Effects of Assertiveness Training and Marital Communication Skills in Enhancing Marital Satisfaction among Baptist Couples in Lagos State, Nigeria (Global Journal of Human-Social Science, 2012)
This study examined the effectiveness of assertiveness training and marital communication skills The moderating effect of length of marriage and number of children were also investigated The study adopted pre-test post-test control quasi-experimental design wish 3 x 2 x 2 factorial matrix Multistage sampling technique was used to select 84 participants representing 42 married couples who were selected from the three local Baptist Churches of the three Baptist conferences in Lagos The comprehensive marital satisfaction scale r 0 98 was the research instrument used One 1 hypothesis was tested at 0 05 level of significance using Analysis of covariance ANCOVA and Duncan post hoe test The study revealed that there was a significant main effect of treatment on marital satisfaction F2 31 19 96 p 0 05 Marital community skills group obtained the highest adjusted post-test mean score on marital satisfaction X 396 29 while the least score was obtained by the control group X 342 91 Based on these findings therefore counselling psychologists marriage counsellors and other professionals working on marriage should make conscious efforts to adopt marital communication skills and assertiveness when managing marital problems and associated challenges Would be couples should also be expose to the two therapist
Keywords: assertiveness training; marital communication skills; marital satisfaction; married couples